2018
DOI: 10.2355/isijinternational.isijint-2018-095
|View full text |Cite
|
Sign up to set email alerts
|

Flow Behavior in the Slab Mold under Optimized Swirling Technology in Submerged Entry Nozzle

Abstract: Flow behavior in the slab mold by optimized swirling flow generation in the submerged entry nozzle (SEN) is investigated. Therefore, hydromechanical model experiment was carried out to simulate this metallurgical process, the effect of turning around the nozzle with swirling and different bottom shape of nozzle is especially analyzed. The flow behavior in the mold was recorded by dye tracer and camera; The two dimension average velocity distribution in the slab mold was measured by the Ultrasound Doppler Veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The fluid flow pattern inside the nozzle could be controlled by adjusting the inner structure of nozzle [70,[114][115][116]150] , using the swirl blade [151,152] , or introducing the electromagnetic swirling flow technology [153] , as illustrated in Figure 13. The structure of the inner surface of nozzles could be designed to annular step [115] , coronal block (also named mogul SEN [150] ), and trapezoidal block [70] .…”
Section: Fluid Flow Control Inside Nozzlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluid flow pattern inside the nozzle could be controlled by adjusting the inner structure of nozzle [70,[114][115][116]150] , using the swirl blade [151,152] , or introducing the electromagnetic swirling flow technology [153] , as illustrated in Figure 13. The structure of the inner surface of nozzles could be designed to annular step [115] , coronal block (also named mogul SEN [150] ), and trapezoidal block [70] .…”
Section: Fluid Flow Control Inside Nozzlesmentioning
confidence: 99%
“…Both the swirl blade and the electromagnetic swirling flow technology illustrated in Fig. 13 are originally applied to improve the uniformity and stability of the outflow from nozzle, stabilize the flow field and temperature distribution and reduce the level fluctuation in the mold [151,153,[155][156][157] . At the same time, when a swirling flow is generated inside the SEN during the continuous casting, both the axial velocity and the tangential velocity of the molten steel near the inner wall of the nozzle are greater, as shown in Figure 14, which is conducive to reducing the thickness of the laminar boundary layer and the scouring of the molten steel on the inner wall of the nozzle, so as to effectively reduce the occurrence of nozzle clogging.…”
Section: Fluid Flow Control Inside Nozzlesmentioning
confidence: 99%
“…The diameter and the transmission frequency of the UDV was 12 mm and 2 MHz, respectively, and the resolution was 2250 ns. Such kinds of measurement methods were well used by us [29,30]. To simulate experiments of the slab continuous casting process of steel under the composite magnetic field, we used 350 kg of molten alloy, as shown in Figure 10a.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…To obtain a desired swirling flow, parameter studies on designs of the swirl blade and nozzle structure were carried out. [26][27][28][29][30][31][32][33] It was found that Swirl number S W increases approximately linearly with a decreased twist ratio. [27] Here, S W is equal to 2W/3U, where W and U are the averaged tangential velocity and axial velocity of the swirling flow, respectively.…”
mentioning
confidence: 99%
“…[29] Also, the concave-bottom swirling flow nozzle can increase the flow velocity at meniscus compared with the convex-bottom nozzle (Figure 2a), which may increase the risk of slag entrainment. [33] For slab, billet and round bloom, steel flow and heat transfer in mold can be further optimized when a divergent nozzle is used, compared with using a straight nozzle. [28,30] Normally, the divergent angle over 100 is preferred to obtain a uniform temperature and velocity distribution in mold.…”
mentioning
confidence: 99%